Polymerization of Substituted Acetylenes Using Well‐Defined Rhodium Complex Catalyst. Chirality Transfer and Amplification in Chiral‐Chiral Block and Random Copolymers. Issue 9 (23rd July 2019) - Goto, Masahide; Nito, Ayaka; Miyagi, Yu; Sanda, Fumio
Abstract: Block and random copolymers are synthesized by the copolymerization of N ‐ tert ‐butoxycarbonyl‐ʟ‐valine 4‐ethynylanilide (1L ) and N ‐ tert ‐butoxycarbonyl‐d‐valine 4‐ethynylanilide (1D ) using [(nbd)Rh{C(Ph) = CPh2 }(PPh3 )]/PPh3 as a catalyst. The size exclusion chromatography (SEC) peaks show narrow polydispersities from the first stage polymerization to the second one in the block copolymerization. Poly(1L 25 ‐ ran ‐1D 25 ) exhibits no circular dichroism (CD) signal, while poly(1L 25 )‐ block ‐poly(1D 25 ) exhibits weak CD signals with the same sign as those of poly(1L 50 ), suggesting the occurrence of chirality transfer from the poly(1L ) block to poly(1D) block. The relationship between the | g | values and1L /1D contents of the block copolymers becomes almost linear at the region of each unit larger than 60%. On the other hand, the relationship between these two factors of the random copolymers is convex upward. Abstract : Chiral‐chiral block copolymers ofl ‐/d ‐valine‐derived optically active phenylacetylene monomers1L and1D, synthesized by the polymerization using a well‐defined rhodium complex catalyst, transfer the chirality from the poly(1L ) block to poly(1D ) block. Random copolymers of1L and1D exhibit chirality amplification, that is, nonlinear relationship between the |g| values and1L /1D unit contents of the copolymers.